Severe Phenotype of APECED (APS1) Increases Risk for Structural Bone Alterations - Laakso, Saila; Borchers, Joonatan; Toiviainen-Salo, Sanna; Pekkinen, Minna; Mäkitie, Outi (Frontiers in Endocrinology, 2020)
Objective: Immunological abnormalities, the resulting endocrinopathies and their treatments may impact bone health in patients with autoimmune polyendocrinopathy–candidiasis–ectodermal dystrophy (APECED, APS1). The aim of the present study was to describe skeletal characteristics in patients with APECED and the prevalence and risk factors of compromised bone health. Patients and methods: We performed a cross-sectional study on 44 patients (27 females) with APECED and 82 age-, gender- and ethnicity-matched control subjects (54 females). We determined the prevalence of osteoporosis by dual-energy X-ray absorptiometry and skeletal characteristics by peripheral quantitative computed tomography at radius and tibia. Results: Patients were examined at the median age of 37.8 years (range, 7.0–70.1). Dual-energy X-ray absorptiometry indicated osteoporosis in four adult patients (9%); radiographs showed vertebral fractures in three patients. The prevalence of multiple non-spinal fractures was higher in patients than in controls. On peripheral quantitative computed tomography, bone characteristics at distal and proximal radius did not differ between the groups. At distal tibia, patients had lower total (p=0.009) and trabecular (p=0.033) volumetric bone mineral density. At the proximal tibia, patients had lower cortical thickness (p<0.001) than controls. Severity of APECED phenotype influenced both radial and tibial characteristics: cortical thickness and total and trabecular volumetric bone mineral density were lower in patients with ≥7 disease manifestations as compared with more mildly affected patients, whose values were similar to controls. Conclusions: APECED associated with bone structural alterations, especially in patients with a high number of disease manifestations. This may increase the risk of fractures with aging, but symptomatic osteoporosis was rare.